Regulatory Perspective of Biosimilars In India - Katla, Sirisha; Kumar, T. M. Pramod; Reddy, V. Yugender; P, Akhilesh. (Asian Journal of Pharmaceutical Research and Development, 2017)
Biosimilar drugs are follow-on versions of original biopharmaceutical medicines. They are independently developed after the patent protecting the original product has expired. Biosimilars are designed to target specific components of immune system as these drugs are capable of targeting proteins in a more specific fashion, yet have lower risks of systemic sideeffects; they have considerable advantages over the older Immunomodulators. As these products are more effective Indian bio-Pharma companies carry the advantages of low cost manufacturing and a highly skilled workforce with global expertise. Biosimilar medicines are intended to have the same mechanism of action for the same diseases as the original biopharmaceutical drug. The regulatory pathway for biosimilars in India was developed jointly by Central drug standard control organisation (CDSCO) & Department of Biotechnology (DBT) through Review Committee on Genetic Manipulation (RCGM).